STRATEGIES FOR USING AROMATHERAPY THROUGH A COMBINATION OF NON-PHARMACOLOGICAL INTERVENTIONS IN THE CHRONIC DISEASE MANAGEMENT PROGRAM (PROLANIS) : SYSTEMATIC REVIEW - Fitriani - - (Fakultas Keperawatan Institut Kesehatan Deli Husada, 2023)
Chronic disease is one of the main causes of premature death worldwide. This study aims to identify and evaluate the use of aromatherapy through a combination of non-pharmacological interventions in PROLANIS. The method used is a systematic review through the ProQuest, PubMed, Science Direct and Google Scholar databases. The selection of articles uses the PRISMA diagram method. This study shows significant results that aromatherapy such as lavender, lemon, peppermint, and rose is widely used in chronic diseases, especially cancer, heart disease, DM, osteoarthritis and CRF for complaints of pain, nausea, vomiting, sleep quality, anxiety and fatigue and pruritus. In conclusion, aromatherapy with a combination of non-pharmacological interventions can help reduce pain, nausea, vomiting, quality of sleep, anxiety and fatigue and pruritus in chronic diseases.